LITERATURE REVIEW ON THE EFFECTIVENESS OF SOCIAL ECONOMY LAW: ANALYSIS AND PRACTICAL IMPLICATIONS - Loso Judijanto; Melyana R Pugu (CV. Adiba Aisha Amira, 2024)
This literature review aims to analyse the effectiveness of social economic law in realising economic justice and improving people's welfare. The study method in this research uses literature. The results show that the effectiveness of social economic law is influenced by factors such as regulatory quality, institutional capacity, public participation, and synergy between stakeholders. Although social economy law has the potential to promote more inclusive economic growth, reduce poverty, and improve people's quality of life, its implementation also faces various challenges, such as conflicts of interest, resistance to change, limited resources, and institutional weaknesses. To optimise the positive impact of social economy law, it requires strong political commitment, transparency, accountability, and active participation from the private sector and civil society. With a comprehensive approach, social economy law can be an effective instrument in realising more equitable, inclusive and sustainable development, and strengthen the foundation for a more stable socio-economic order in the future.